2012
DOI: 10.1080/03670244.2012.635570
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Knowledge of Four Leafy Vegetables Used by Rural Populations in Benin

Abstract: Leafy vegetables are sources of diet diversification and could contribute to food and nutritional security in African rural areas. However, in some places, little is known about if, how, and why leafy vegetables are consumed. Processing and preservation methods, food forms, and consumption determinants of four leafy vegetables (Sesamum radiatum, Ceratotheca sesamoïdes, Acmella uliginosa and Justicia tenella), known to contribute to the diet of rural populations in the Center and Northern parts of Benin, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
3
8
0
1
Order By: Relevance
“…The information collected during this research indicates beneficial properties related to use of traditional leafy vegetables in household food systems. These findings confirm the findings of others who have reported on the dietary and medicinal benefits of leafy vegetables [19,5,2,8,9,11,10,17,12]. Amaranth, African basil and African eggplant were the most consumed by respondent; findings consistent with [2] who also determined that Amaranth, African basil and African eggplant were amongst the top five of frequently used leafy vegetables in all phyto-geographical zones of Republic of Benin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The information collected during this research indicates beneficial properties related to use of traditional leafy vegetables in household food systems. These findings confirm the findings of others who have reported on the dietary and medicinal benefits of leafy vegetables [19,5,2,8,9,11,10,17,12]. Amaranth, African basil and African eggplant were the most consumed by respondent; findings consistent with [2] who also determined that Amaranth, African basil and African eggplant were amongst the top five of frequently used leafy vegetables in all phyto-geographical zones of Republic of Benin.…”
Section: Discussionsupporting
confidence: 90%
“…Consumption of Amaranth, African basil and African eggplant, in southern part of the country, was related to ethno-botanical knowledge of socio-cultural groups [6]. Similar observations were made by [19] and [17] on consumption of other traditional green leafy vegetables in northern areas of the country. Likewise, previous reports demonstrated that dietary habits depended on interactions between foods availability, cultural identity, geospatial environment and consumers' spending power [19,5,2,6,20].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Indeed, in a rural area, endogenous knowledges being more preserved [150], people resort, culturally, to the use of traditional medicine and herbal drugs are socioeconomically acceptable [151,152]. …”
Section: Discussionmentioning
confidence: 99%
“…L'espèce est actuellement en cours de domestication par les populations rurales au Bénin (Etèka et al 2011). Hormis quelques travaux conduits sur la sélection de sites pour la conservation in situ, la germination des semences, et les connaissances endogènes des populations sur les propriétés culinaires (Adéoti et al 2009;Etèka et al 2010;Vihotogbé-Sossa et al 2012). Aucune étude n'a encore été réalisée sur la biologie des plants de l'espèce au Bénin.…”
Section: Discussionunclassified